An Investigation of the Determinants of Engineering Aptitude Using Structural Equation Modeling - M. S. Firdaus; Deliansyah Pasayu (Journal of Pedagogy and Education Science, 2026)
The urgency of this research is a follow-up to previous research that identified moderate engineering aptitude among engineering students at Universitas Islam Ogan Komering Ilir Kayuagung. Therefore, further analysis of the factors influencing engineering aptitudes is necessary. The results of this research will have implications for curriculum development, instructional design, and learning environments that can support engineering aptitude in engineering students and ensure success in the workforce. This study aims to determine a model of factors influencing engineering aptitude in engineering students.  This research is a quantitative cross-sectional study. The sampling technique used was purposive sampling, involving 30 mechanical engineering students and  72  civil engineering students from the Faculty of Engineering at Universitas Islam Ogan Komering Ilir Kayuagung. The data were analyzed using Structural Equation Modelling (SEM). The SEM analysis included testing the measurement model and evaluating the structural model. Based on the research results, it can be concluded that engineering students' engineering aptitude is influenced by problem-solving and mechanical reasoning. Therefore, the study emphasizes the crucial role of mechanical reasoning and problem-solving processes in developing engineering aptitude among students. From a practical perspective, the findings suggest that engineering education should provide learning environments that actively encourage reasoning skills and real-world problem-solving experiences.